O papel encapsulador das expressões referenciais metafóricas e/ou metonímicas - Sousa, Márcia Ananda Soares Siqueira de (2021)
Supported by research such as those of Lima (2013), Sousa (2012) and Sousa and Lima (2015), who advocate in favor of a broader notion of encapsulation, in the context of Textual Linguistics, in which the cognitive elements intrinsic to the phenomenon are described and interpreted, this thesis proposes to characterize an encapsulating function of referential expressions, explaining their metaphorical and / or metonymic semanticcognitive basis. Starting from the hypothesis of the cognitive-discursive nature of encapsulation, we resort to an interface between Textual Linguistics and Cognitive Linguistics, given the complexity and dynamics of this referential process, in descriptive and explanatory terms. For the construction of this interface, we used the Theory of Idealized Cognitive Models (LAKOFF, 1987) and collaborators, whose basic assumption is that knowledge is organized through structures called Idealized Cognitive Models (ICMs), understanding that the structure of categories and the prototypical effects are the result of this organization. Under these foundations, we analyzed 10 texts that belong to the textual genre news and that present the nominal expressions “Caso Pesseghini”, “O triste episódio de Castelo do Piauí”, “O caso Mensalão”, “O caso Viúva Negra”, “O episódio de Pinheirinho”, “O caso Favela Naval”, “A operação Xepa”, “A operação Bumerangue”, “A operação Boneco” e “A operação Jabuti”, which designate facts and/or police events. From a methodological point of view, we partially follow the analysis proposal prepared by Lima (2009), in which we rely on the treatment of the cognitive aspects inherent to these nominal expressions. For a more inductive procedure, we analyze the textual behavior of such expressions, which can function as "introductions" or "anaphors", performing, in the news, argumentative functions such as "guiding a point of view" and "foreseeing / anticipating the theme / subject matter". The results of the analysis point to the validation of the formulated hypotheses, since the explanation of the semantic-cognitive processes elucidates the ways in which the interlocutor can (re)build the semantic associations established in the text and the relationships between the referents in the network.